101k views
5 votes
[9 X (10 – 2)] = [2 + (5 x 2)]

User Juan Marco
by
5.8k points

1 Answer

1 vote

Answer:

x=3

Explanation:

Simplifying

9 + -2(x + -5) = x + 10

Reorder the terms:

9 + -2(-5 + x) = x + 10

9 + (-5 * -2 + x * -2) = x + 10

9 + (10 + -2x) = x + 10

Combine like terms: 9 + 10 = 19

19 + -2x = x + 10

Reorder the terms:

19 + -2x = 10 + x

Solving

19 + -2x = 10 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.

19 + -2x + -1x = 10 + x + -1x

Combine like terms: -2x + -1x = -3x

19 + -3x = 10 + x + -1x

Combine like terms: x + -1x = 0

19 + -3x = 10 + 0

19 + -3x = 10

Add '-19' to each side of the equation.

19 + -19 + -3x = 10 + -19

Combine like terms: 19 + -19 = 0

0 + -3x = 10 + -19

-3x = 10 + -19

Combine like terms: 10 + -19 = -9

-3x = -9

Divide each side by '-3'.

x = 3

Simplifying

x = 3

User Pistachio
by
5.9k points